2018
DOI: 10.2146/ajhp161021
|View full text |Cite
|
Sign up to set email alerts
|

Minimizing opioid use after acute major trauma

Abstract: Targeted provider and patient education on minimizing opioid use was associated with a reduction in MME on discharge from the hospital after traumatic injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 17 publications
0
28
0
Order By: Relevance
“…A study of inpatient opioid use found that the proportion of patients receiving slow release opioids declined from 35% to 16% following an education intervention, and that of patients discharged without opioids increased from 9% to 13%. 21 Other studies have reported that prescribed daily opioid doses declined by one-half following educational interventions. 20,22 The reductions in our study were less pronounced, but the median baseline dose was lower (30 mg daily oral morphine equivalent) than in previous studies (150 mg, 20 90 mg 21 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A study of inpatient opioid use found that the proportion of patients receiving slow release opioids declined from 35% to 16% following an education intervention, and that of patients discharged without opioids increased from 9% to 13%. 21 Other studies have reported that prescribed daily opioid doses declined by one-half following educational interventions. 20,22 The reductions in our study were less pronounced, but the median baseline dose was lower (30 mg daily oral morphine equivalent) than in previous studies (150 mg, 20 90 mg 21 ).…”
Section: Discussionmentioning
confidence: 99%
“…21 Other studies have reported that prescribed daily opioid doses declined by one-half following educational interventions. 20,22 The reductions in our study were less pronounced, but the median baseline dose was lower (30 mg daily oral morphine equivalent) than in previous studies (150 mg, 20 90 mg 21 ). Similarly, the reductions in quantities supplied were not as pronounced as in previous studies, 20,22,24 but the baseline quantities were also lower in our study; this is unsurprising, as opioids are now prescribed in smaller quantities because of growing awareness of the potential harms and poor functional outcomes associated with their long term use.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the conjoined priorities of appropriately treating severe pain during ICU/hospital stays and ameliorating opioid overuse and abuse, it is not surprising that efforts by hospitals to control the opioid epidemic have focused on limiting inappropriate opioid prescribing at patient discharge, since prescribing at discharge has been shown to contribute to chronic opioid use in opioid‐naïve patients . Furthermore, data from the CDC demonstrates that approximately 10% of fatal overdoses occur in patients released from institutional settings in the month preceding the overdose .…”
Section: Implications Of the Opioid Epidemic For Critical Care Practimentioning
confidence: 99%
“…A literature search has identified efforts in multiple disciplines where pain control has been improved for trauma inpatients. Multiple modes of analgesia have been shown to improve acute pain control6 and targeting prescriber education has been demonstrated to improve practice 7…”
Section: Introductionmentioning
confidence: 99%